Between Aesthetics and Pedagogy: Audience Training and Proletarian Education in Gramsci’s Theatre Chronicles - Pozzoni, Maria Chiara (International Gramsci Journal, 2025)
The literature that has dealt with Antonio Gramsci’s theatre chronicles has often given them a teleological interpretation with respect to the Prison Notebooks, as if these were to be read as the organic and accomplished formulation of the ideas expressed in the chronicles. Ample space was dedicated to the author’s confrontation with the main protagonists of the Turin theatre scene of the 1910s, with the result that the focus was mainly on the critic’s point of view rather than on his relationship with the audience. The pedagogical theme, which pertained strictly to theatre in Gramsci’s political project, has thus generally taken a back seat. This text attempts to trace in his youthful writings the plot of the educational project that Gramsci attributed to theatre and theatre criticism. To do so, it investigates his conception of the audience and its education, starting with an analysis of the taste prevalent in the different social classes at the time and Gramsci’s criticism of profit as a motive for theatrical work. In this way, the project of a disinterested aesthetic education is reconstructed, at the same time conforming to the potential of the theatre and oriented towards the formation of the proletariat as an aesthetic and political subject.